MARITAL STRAIN AND PSYCHOLOGICAL DISTRESS IN SAME-SEX AND DIFFERENT-SEX COUPLES - Garcia, Michael A. (J Marriage Fam, 2019)
OBJECTIVE: This study examines the association of marital strain − as reported by each spouse − with psychological distress and considers whether the associations vary for men and women in gay, lesbian, and heterosexual marriages. BACKGROUND: Prior studies show that marital strain is associated with psychological distress. However, most studies rely on only one spouse’s perspective and do not consider how appraisals of strain from both spouses may contribute to distress. Moreover, possible gender differences in these associations have been considered only for heterosexual couples. METHOD: Analyses are based on 10 days of dyadic diary data from 756 midlife U.S. men and women in 378 gay, lesbian, and heterosexual marriages. Multilevel modeling is used to examine the association of self- and spouse-reported marital strain with psychological distress; actor-partner interdependence models (APIM) explore possible gender differences in these associations. RESULTS: Both self- and spousal-reports of marital strain are associated with psychological distress, with notable gender differences. The associations of self- and spouse-reported marital strain with distress are stronger for women in different-sex marriages when compared to men in same-sex and different-sex marriages. The association is also stronger for women in different-sex marriages compared to women in same-sex marriages, but for self-reported strain only. CONCLUSION: Marital appraisals by both spouses are important for psychological well-being and may be especially important for the well-being of women in different-sex marriages.